Preparation and carbon emission analysis of high-performance pavement concrete using waste gypsums - Wang, Hui; Xu, Fengxia; Liu, Zhen; Zhong, Shunjie; Xing, Enkuo; Ye, Yongbin; Zhao, Yan; Li, Chenjiang (Frontiers in Materials, 2025)
This study explores the potential of waste gypsum, specifically phosphogypsum (PG) and desulfurization gypsum (DG), as alternative materials in supersulfated cement-based concrete (SSCC) for low-carbon road construction. The research comprehensively investigates the effects of PG and DG on the mechanical properties, corrosion resistance, and water resistance of SSCC. Additionally, the hydration kinetics and microstructure of SSC are analyzed through isothermal calorimetry, X-ray diffraction, and scanning electron microscopy. The findings show that PG-modified SSCC outperforms DG-modified SSCC, with 26.9% and 28% improvements in compressive and flexural strengths, respectively. Both PG and DG contribute to enhanced corrosion resistance, particularly in acidic environments, due to the formation of distinct hydration products compared to traditional concrete. Microstructural analysis reveals denser structures with Ettringite (AFt) and calcium silicate hydrate. Moreover, the hydration process of SSC exhibits low heat release, mitigating cracking risks in outdoor applications. A comprehensive evaluation indicates that PG-modified SSCC not only offers superior mechanical properties but also demonstrates significantly reduced carbon emissions and energy consumption, highlighting its potential as a sustainable material for road concrete.